Leadership and management tools for the new nurse : a case study approach - Marquis, Bessie L.; Huston, Carol Jorgensen (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Adaptation of: Leadership roles and management functions in nursing. 7th ed. c2012